1985
DOI: 10.1002/eji.1830150116
|View full text |Cite
|
Sign up to set email alerts
|

Clones of B lymphocytes in individual follicles of the bursa of Fabricius

Abstract: To discover whether individual bursal follicles can contain clones of B lymphocytes, we estimated the numbers of lymphoid cell precursors populating single follicles in two types of chicken chimera. The first type was produced by establishing parabiotic connections between blood vessels of embryo chorioallantoic membranes. Under these conditions, and most likely during normal development, most follicles are populated by more than one, but less than ten, precursor cells. However, in a second type of chimera, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 13 publications
5
61
0
Order By: Relevance
“…The oligoclonal development of individual bursal follicles has also been reported in the chicken [7,88]. In contrast, the clonality of jejunal PP follicles is not yet clear and it needs further analysis.…”
Section: Prenatal Development Of Ileal and Jejunal Ppmentioning
confidence: 98%
“…The oligoclonal development of individual bursal follicles has also been reported in the chicken [7,88]. In contrast, the clonality of jejunal PP follicles is not yet clear and it needs further analysis.…”
Section: Prenatal Development Of Ileal and Jejunal Ppmentioning
confidence: 98%
“…Several experimental approaches have demonstrated that the B cells in each follicle are derived from a limited number (two to five) of sIg ϩ precursors and, further, that there is no traffic of B-lineage cells from one follicle to another (10,20,21). As a consequence, the increase in bursal cellularity observed after about embryonic day 15, when most immigration of B cell precursors to the bursa has ended, represents the consequences of B cell division within the bursa.…”
Section: Perinatal Deletion Of B Cells Expressing Surface Ig Moleculementioning
confidence: 99%
“…The bursa is colonized by a single wave of B cell precursors during embryogenesis starting at about embryonic day 8 (E8) and lasting about a week (11). Within the bursa, B cell precursors first are observed in the mesenchymal tissue, and 20,000-40,000 precursors subsequently migrate across the bursal epithelial basement membrane and begin to proliferate in oligoclonal clusters or epithelial buds from which the discrete follicles of the mature bursa are derived (12,13).…”
mentioning
confidence: 99%